Perancangan Sistem Informasi Obat Generik “sioge” di Desa Pampang - Herliana Rosika; Mahayadi; Idham; Wahyu Ramadhan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
According to the 2010 Regulation of the Minister of Health of the Republic of Indonesia, generic drugs are drugs with the official name International Non-Proprietary Names (INN) specified in the Indonesian Pharmacopoeia or other standard books for the beneficial substances they contain. Where generic drugs with trade names that use the name of the drug manufacturer concerned. Objective: To find out an analysis of people's perceptions and dependence on generic drugs in Pampang Village, Central Lombok Regency including definition, price, quality, access to related drug information from the quantity of generic drugs that people often buy, to create an Android-based application system to facilitate access to drug information related government regulations. Method: Using the Interview method using the face to face method for data collection in the form of a comparison table. Results: Of the 69 respondents, only 1 respondent had a good perception of the meaning of generic drugs and trademarked drugs with a percentage of 1.4%, and 43 respondents had an adequate perception with a percentage of 62.3%, while as many as 25 respondents had less knowledge with a percentage 36.2%. Conclusion: That the analysis of community perceptions and dependence on generic drugs in Pampang Village can be categorized as sufficient